PENGARUH PEMBERIAN BOKASHI KELADI DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG SUNA (Allium chinense G. Don) PADA TANAH SPODOSOL - Asie E.R; Rhayna E; Usup A (AgriPeat, 2020)
The purpose of this research was to determine and examine the interaction between taro bocashi and the spacing arrangement of growth and yield of onion suna plants, to find out and study the effect of taro bokashi and spacing on the growth and yield of suna on spodosol soil. This research was conducted in Banturung Village, Bukit Batu Subdistrict, Palangka Raya City from February to June 2019. This study used a factorial Randomized Block Design with two factors. The first factor is giving bokashi taro consisting of 4 levels, namely B0 = without bocashi (control), B1 = 5 ton ha-1 , B2 = 10 ton ha-1, and B3 = 15 ton ha-1 . The second factor is spacing consisting of 3 levels, namely J1 = 10 cm × 10 cm, J2 = 10 cm × 15 cm, and J3 = 15 cm × 20 cm. The two treatment factors combined as experimental treatments consisted of 12 experimental combinations and then repeated 3 times. Observations for growth variable (number of leaves clump-1) were carried out at 14, 21, 28, 35 and 42 days. Variables observed for yield were number of tubers clump-1, fresh weight clump-1, and fresh weight plot-1 . Root adhering soil (RAS) observed after harvest. The collected data were analyzed by analysis of variance and continued with the Tukey’s HSD 5% if it had a significant effect. The results is no interaction between taro bokashi and spacing on the growth and yield variables of suna onion. The treatment of taro bokashi of 10 tons ha-1 gave a better influence on the number of leaves at the age of 14 days and RAS value. Setting the best spacing at 10 cm × 10 cm produces a fresh 7.40 tons ha-1 .